A Laboratory Approach Consideration for Thrombotic Risk Assessment in Transfusion-dependent Beta-thalassemia Major Utilizing Complete Blood Count Cell Population Data and Basic Screening Hemostatic Parameters - R. Yashica Gowda; Jayaraj G. Gudi; Ravindra Y. Mandolikar; Karthik Srevatsa; Ranjit P. Kangle; Sujata M. Jali (Journal of the Scientific Society, 2024)
Objective: The objective of the study was to evaluate prothrombin time/international normalized ratio (PT) along with activated partial thromboplastin time (APTT) and its association with platelet and red blood cell (RBC) cell population data for initial assessment of thrombotic tendencies. Materials and Methods: Blood samples of 43 patients diagnosed with a beta-thalassemia major who were transfusion dependant were taken for assessment of mean platelet volume (MPV), plateletcrit (PCT), and platelet distribution width (PDW) along with RBC distribution width and correlated with APTT. Results: Elevated APTT and PT were noted among patients with thalassemia along with elevated PCT and red cell distribution width-coefficient of variation (RDW-CV). Reduced PDW was noted. Elevated APTT was positively associated with RDW and MPV and negatively associated with PDW and PCT. Conclusion: In our study, elevated levels of PCT RDW CV, PT, and APTT were observed. Elevated levels of APTT were also noted to be positively correlated with MPV and RDW CV.